The Thomas Indian School and the "Irredeemable" Children of New York - Burich, Keith R. (Book collections on Project MUSE., 2016)
"The story of the Thomas Indian School is the story of the Iroquois people and the suffering and despair of the children who found themselves trapped in an institution from which there was little chance for escape. Although the school began as a refuge for children, it also served as a mechanism for "civilizing" and converting native children to Christianity. As the school's population swelled and financial support dried up, the founders were forced to turn the school over to the state of New York. Under the State Board of Charities, children were subjected to prejudice, poor treatment, and long-term institutionalization, resulting in alienation from their families and cultures. In this harrowing yet essential book, Burich offers new and important insights into the role and nature of boarding schools and their destructive effect on generations of indigenous populations."--Back cover